THE STUDY OF PIT AND FISSURE SEALANTS CONCERNING WATER SORPTION AND SOLUBILITY - CORNEA, Daniela; SILAGHI-DUMITRESCU, Laura; BALAZSI, Robert; OPREAN, Radu; DUDEA, Diana; MOLDOVAN, Mărioara (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Improved dental materials are a requirement in these modern times, because of the highly percent of dental decay found in children. Four commercial pit and fissure sealants have been studied in respect of water sorption and solubility (1, 3, 7 and 14 days). These measurements prove the stability of a material, as well as the adhesion to enamel and the resistance to wear. The materials taking into account are two resin- based sealants - Fotoseal® (Babeş-Bolyai University, Raluca Ripan Chemistry Research Institute), Fissurit FX® (VoCo), one gass-ionomer - Fuji Triage® (GC Fuji) and one compomer - Dyract Seal® (Dentsply). The statistical analysis used a Mixt ANOVA design, with the significance level set at p ≤0.01. Firstly, there were analised the differences between the days of measurement, without taking into account the material type. Secondly, there were examined the differences between materials and finally, the interaction between material type and day of measurement. We also calculated the magnitude of the clinical effect of material type, on each of the days of measurement. Differences in chemical composition determine a modified behavior of these materials. The results showed that Fissurit FX had the lowest values of water sorption and solubility, closely followed by Fotoseal. Dyract Seal had higher values. In the same time, Fuji Triage showed the highest rates for water sorption and a fluctuant behavior concerning solubility, with increased level in the first day of measurement, decreased values in the next days (3, 7) and another small enhancement in the last day of measurement (14).